Oncology monoclonal antibodies expenditure trends and reimbursement projections in the emerging Balkan market - Jakovljevic, Mihajlo B (Farmeconomia. Health economics and therapeutic pathways, 2014)
Monoclonal antibodies applied in clinical oncology present a therapeutic promise for many patients with cancer. Nevertheless these expensive protocols are associated with extremely high acquisition and administration costs. The issue of societal affordability of such treatment options is particularly at stake among middle income European economies. Medicines Agency of Serbia issues regular annual reports on public expenditure on pharmaceuticals since 2004. According to these official data total public expenditure on drugs doubled from 2004-2012 (from € 339,279,304 to € 742,013,976). During the same nine years public expenditure on antineoplastic pharmaceuticals was rising at much faster pace, approximately five times from € 10,297,616 in 2004 to € 51,223,474 in 2012. Absolutely record growth belongs to the value of turnover of monoclonal antibodies indicated in diverse malignancies. These costs became almost twenty times higher in 2012 compared to 2004 (€ 19,687,454 towards € 1,033,313 in the past). National pharmaceutical expenditure trend projections in this country show strong recovery in 2012 after severe blow to the overall health care market imposed by the worldwide crisis. Universal health insurance coverage and sustainable health care financing provision will remain difficult issues for Balkan economies in years to come. Although monoclonal antibodies exhibit undisputed therapeutic efficiency in certain malignant disorders, cost-effectiveness estimates must be taken into consideration by policy makers deciding on reimbursement.